Processes for Implementing Community Health Worker Workforce Development Initiatives - Barbero, Colleen; Mason, Theresa; Rush, Carl; Sugarman, Meredith; Bhuiya, Aunima R.; Fulmer, Erika B.; Feldstein, Jill; Cottoms, Naomi; Wennerstrom, Ashley (Frontiers in Public Health, 2021)
Introduction: The objective of this observational, cross-sectional study was to identify, document, and assess the progress made to date in implementing various processes involved in statewide CHW workforce development initiatives. Methods: From September 2017-December 2020, we developed and applied a conceptual model of processes involved in implementing statewide CHW initiatives. One or more outputs were identified for each model process and assessed across the 50 states, D.C., and Puerto Rico using peer-reviewed and grey literature available as of September 2020. Results: Twelve statewide CHW workforce development processes were identified, and 21 outputs were assessed. We found an average of eight processes implemented per state, with seven states implementing all 12 processes. As of September 2020, 45 states had a multi-stakeholder CHW coalition and 31 states had a statewide CHW organization. In 20 states CHWs were included in Medicaid Managed Care Organizations or Health Plans. We found routine monitoring of statewide CHW employment in six states. Discussion: Stakeholders have advanced statewide CHW workforce development initiatives using the processes reflected in our conceptual model. Our results could help to inform future CHW initiative design, measurement, monitoring, and evaluation efforts, especially at the state level.